Inflammation preservation strategy: reconciling pain control and disc resorption in lumbar disc herniation - Gong, Guanyi; Yan, Zheng; Lai, Qilong; You, Peijie; Yu, Pengfei; Li, Xiaochun; Wang, Zhiqiang; Lin, Shun; Dai, Yuxiang; Jiang, Hong; Liu, Jintao (Frontiers in Immunology, 2025)
Lumbar disc herniation (LDH) is a prevalent condition driven by inflammation, which mediates both radicular pain and spontaneous resorption of herniated material. Traditional anti-inflammatory therapies alleviate pain but may impede disc regression. We propose an Inflammation Preservation Strategy (IPS) to harness inflammation’s reparative potential while managing symptoms. Molecular, clinical, and translational evidence reveals inflammation drives resorption in 60–90% of LDH cases. Key mechanisms include neovascularization, dynamic macrophage polarization (where M1 degrades matrix while M2 promotes repair), and apoptosis-autophagy synergy. Traditional anti-inflammatory therapies risk suppressing this reparative cascade, whereas IPS advocates precision modulation—avoiding pan-anti-inflammatory agents during acute phases and employing targeted interventions to balance analgesia with tissue healing. Clinical data support IPS in achieving near-complete resorption and sustained pain relief, suggesting a paradigm shift from symptomatic palliation to disease-modifying regeneration. Future directions include real-time inflammation phenotyping and smart biomaterials to advance precision IPS implementation.